Pengaruh Iklim Komunikasi Organisasi dan Sistem Penghargaan terhadap Kinerja Karyawan - Agasta, Hardikna (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2019)
The development of the tourism industry in Surabaya has also made the hotel industry grow. The performance of hotel employees in providing services contributes to the development of the tourism industry in Surabaya. Papilio's Best Western Hotel was chosen as the research object because it was one of the best hotels in Surabaya, even in Indonesia according to the Director of National Hospitality. In addition, the Best Western Papilio Hotel has received various achievements from various online travel agents that are rarely obtained by other hotels. This achievement is the result of employee performance. Whether or not the employee's performance is influenced by several factors including the communication climate and reward system. The organizational communication climate and reward system contribute greatly to the success and performance of the organization. By knowing that the organizational communication climate and reward system affect employee performance, organizations can improve communication and reward systems accordingly so as to improve the performance of employees. Therefore, the focus of this research is to explain the influence of the organizational communication climate and the system of rewards for the performance of employees of the Best Western Papilio Hotel Surabaya.The theory used in this study is the organization's internal communication theory, organizational communication climate, reward system, and performance. This study uses an explanative quantitative approach using the survey method. The survey was conducted by distributing questionnaires to 104 employees of the Best Western Papilio Hotel Surabaya. The results of this study show that simultaneously the communication climate and reward system have an influence on the performance of employees of the Best Western Papilio Hotel in Surabaya by 30.2% and the remaining 69.8% influenced by other factors not examined in this study